(untitled) (UNED Research Journal, 2017)
Wetlands maintain high biodiversity and provide important habitat for many bird species, but now have strong pressure from anthropogenic activities. Birds in wetlands are important indicators of environmental changes and our goal was to characterize the bird community in the wetlands Palustrine Corral de Piedra as a mechanism for conservation of tropical dry forest of Costa Rica. We used point counts to describe bird richness and abundance in open (lakes and flooded grasslands) and wooded areas. We described habitat use and microhabitats, trophic guilds, biogeographic distribution and status in Costa Rica. We recorded 83 species of resident birds belonging to 36 families, of which 65 are resident species and 18 have some migratory status in Costa Rica. Secondary consumer species of small vertebrates corresponded to 45,8% and primary consumers were 25,3%. The birds mainly used trees for perching but use emergent shrubs, floating vegetation and water. We found a large number of Egrets, Flycatchers and Hawks playing important roles as pollinators, seed dispersers and predator is adding significant value to the ecological dynamics of forests and lakes in the area. Corral de Piedra has special importance as a site for the establishment of migratory birds and large number of resident species of conservation concern. We consider that joint efforts between residents and researchers are an important tool for bird conservation in the region.